(untitled) (Biological Sciences - PJSIR, 2005)
The review deals with the need to treat industrial effluents before their discharge into open water bodies. The technical and economical problems associated with conventional water treatment procedures have been pointed out. Biosorption, as an alternative technology for metal remediation of wastewaters is discussed. A detailed description of the theoretical basis, fundamental concepts and mechanisms involved in the adsorption of metals has been given. The validity of biosorption data as determined by the fit on the mathematical models of Freundlich and Langmuir adsorption isotherms has been described. The ion exchange mechanism, its differences with the Langmuir adsorption isotherms mechanism, and the advantages of one mechanism over the other in understanding the concepts of the biosorption process have been considered.